Coordenação pedagógica na escola : uma função para pedagogos? - Oliveira, Matildes Aparecida Trettel de (2015)
The survey "Pedagogical coordination in school: a role for educators?" is the result of an initial personal uneasiness about the meaning and the importance of the professional educator in the exercise of its function pedagogical and school service in specially pedagogical coordination, because, in Mato Grosso, the State Department of Education – SEDUC – MT through its normative has prioritized the licensed in Pedagogy to assume the function of pedagogical coordinator in the State public schools. In this way, the goal is to "Investigate how the pedagogical coordinators in education graduates not appropriate pedagogical knowledge in the exercise of their function", with the proposal to respond to the following problem: “As the pedagogical coordinators in education graduates not appropriate knowledge of pedagogy for the exercise of their function?” This research is a qualitative research and dialectic of a significant aspect of school education – pedagogical coordination – and its methodological procedure to conduct exploratory research, descriptive, bibliographical and documentary. In relation to the research tool used to conduct interviews. The development of research in six state of urban public schools Tangará da Serra – MT, having as subject seven teachers who exercise the function of pedagogical coordinators, whose selection obeyed the following criteria: not be graduated in Pedagogy and exercise for more than three years the pedagogical coordinator function. Among the studies that support for this research we use André (2014), Cambi (1999), oak (2005, 2006, 2008), Franco (2003, 2005, 2008, 2012), Freire (1980, 1983, 1991, 1992, 1993, 2008) Garrido (2009), Libâneo (2002, 2004, 2010), Nóvoa (1992, 1998, 2007), Pinto (2006), Placco (2010), Saviani (2007), Tardif (2004), Vaishya (2011), Veiga (1998) among others, which constitute fundamental theoretical supports for the analysis.The research highlights the importance of a professional enabled in pedagogy for the exercise of the function of pedagogical coordinator. This evidence is perceived by the affirmation of various pedagogical coordinators, as well as by indications that point theorists studying Pedagogy and educational sciences.